ACM SIGGRAPH 2004 Papers 2004
DOI: 10.1145/1186562.1015804
|View full text |Cite
|
Sign up to set email alerts
|

A stereo display prototype with multiple focal distances

Abstract: Typical stereo displays provide incorrect focus cues because the light comes from a single surface. We describe a prototype stereo display comprising two independent fixed-viewpoint volumetric displays.Like autostereoscopic volumetric displays, fixedviewpoint volumetric displays generate near-correct focus cues without tracking eye position, because light comes from sources at the correct focal distances. (In our prototype, from three image planes at different physical distances.) Unlike autostereoscopic volum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
120
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(120 citation statements)
references
References 25 publications
0
120
0
Order By: Relevance
“…It has been shown that people prefer depth-of-field (DoF tion of focal-cues can be seen as a substitute for a multifocal plane display [AWGB04], which poses a huge technical challenge to build. To achieve gaze-contingent DoF visualisation, we implemented the DoF rendering algorithm based on the reverse mapping technique with reduced colour leakage [PC83, MBT11].…”
Section: Focal-cues Inductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that people prefer depth-of-field (DoF tion of focal-cues can be seen as a substitute for a multifocal plane display [AWGB04], which poses a huge technical challenge to build. To achieve gaze-contingent DoF visualisation, we implemented the DoF rendering algorithm based on the reverse mapping technique with reduced colour leakage [PC83, MBT11].…”
Section: Focal-cues Inductionmentioning
confidence: 99%
“…However, if we could precisely predict the gaze position, we could not only gain a very effective pointing device, but also enhance display with gaze contingent capabilities. For example, accommodation related focal cues could be simulated to enhance the visual experience [HLCC08] without a need for multi-focal displays [AWGB04].…”
Section: Introductionmentioning
confidence: 99%
“…This causes vergence-accommodation rivalry, where the eyes converge on an object but the lens accommodates on the screen level where the image is sharpest [36], [56]. When the cues are consistent the perception of depth on a stereoscopic display becomes significantly faster [62].…”
Section: B Portable Autostereoscopic Displaysmentioning
confidence: 99%
“…Recently, vari-focal and multi-focal plane stereo displays have been proposed as a remedy to the above-described focus cue problem [47][48][49][50][51][52][53][54][55][56][57] , either by providing dynamic control of the focal distance through an active optical method [47][48][49][50] presenting multiple focal planes at different focal distances [49][50][51][52][53][54][55][56] . Different from volumetric displays [57][58][59] in which all voxels within a volumetric space have to be rendered at a flicker-free rate regardless of the viewer's point-of-interest (PoI), these vari-focal or multi-focal approaches are relatively more computationally efficient, while being able to reduce the discrepancy artifacts to various extents.…”
Section: Emerging Technologies: Vari-focal and Multi-focal Plane Dispmentioning
confidence: 99%
“…For instance, Schowengerdt and Seibel demonstrated a dual-focal plane see-through retinal scanning display (RSD) implemented with a deformable membrane mirror (DMM) device 51 . Akeley et al presented a proof-of-concept display prototype by using a stack of three display planes, which were created by optically splitting an LCD panel into three sub-regions that appear to be placed along the visual axis with an equal spacing of 0.67 diopter53 . More recently, Lee et al demonstrated a depth-fused 3-D (DFD) display prototype by projecting 2-D images onto multiple immaterial FogScreens, with either a stack or an L-shaped configuration55 .…”
mentioning
confidence: 99%